Planning the training - Thilbert, H. (The Professional Skater PS Magazine, 2008)
The purpose of a TRAINING PLAN is to identify the work to be carried out to achieve agreed objectives between the coach and the skater. Training plans should be drawn up to identify long term (3-5 years) objectives as well as short term plans for the forth coming season. The topic concentrates on the development of the short term annual training plan. In its simplest form the plan could comprise a single sheet identifying the overall plan for the year, and more detailed weekly plans identifying the specific activities the skater is to carry out.